A single-chain variable fragment intrabody prevents intracellular polymerization of Z α(1)-antitrypsin while allowing its antiproteinase activity - Ordóñez, Adriana (FASEB J, 2015)
Mutant Z α(1)-antitrypsin (E342K) accumulates as polymers within the endoplasmic reticulum (ER) of hepatocytes predisposing to liver disease, whereas low levels of circulating Z α(1)-antitrypsin lead to emphysema by loss of inhibition of neutrophil elastase. The ideal therapy should prevent polymer formation while preserving inhibitory activity. Here we used mAb technology to identify interactors with Z α(1)-antitrypsin that comply with both requirements. We report the generation of an mAb (4B12) that blocked α(1)-antitrypsin polymerization in vitro at a 1:1 molar ratio, causing a small increase of the stoichiometry of inhibition for neutrophil elastase. A single-chain variable fragment (scFv) intrabody was generated based on the sequence of mAb4B12. The expression of scFv4B12 within the ER (scFv4B12(KDEL)) and along the secretory pathway (scFv4B12) reduced the intracellular polymerization of Z α(1)-antitrypsin by 60%. The scFv4B12 intrabody also increased the secretion of Z α(1)-antitrypsin that retained inhibitory activity against neutrophil elastase. MAb4B12 recognized a discontinuous epitope probably located in the region of helices A/C/G/H/I and seems to act by altering protein dynamics rather than binding preferentially to the native state. This novel approach could reveal new target sites for small-molecule intervention that may block the transition to aberrant polymers without compromising the inhibitory activity of Z α(1)-antitrypsin.—Ordóñez, A., Pérez, J., Tan, L., Dickens, J. A., Motamedi-Shad, N., Irving, J. A., Haq, I., Ekeowa, U., Marciniak, S. J., Miranda, E., Lomas, D. A. A single-chain variable fragment intrabody prevents intracellular polymerization of Z α(1)-antitrypsin while allowing its antiproteinase activity.